Anaesthesia, Pain, Intensive Care and Emergency Medicine — A.P.I.C.E. Proceedings of the 11th Postgraduate Course in Critical Care Medicine Trieste, Italy — November 11–16, 1996 - Gullo, Antonino (Springer Milan, 1997)
At the APICE '96 research scientists and clinicians were provided with updated guidelines for the treatment of patients with acute and chronic critical conditions. This volume contains 100 chapters,in which the main pathophysiological concepts were reviewed, with special emphasis on the cardiovascular, respiratory, metabolic, and neurologic systems. Special reference is made to the pharmacologic and biotechnologic strategies currently being used to support those vital functions that are affected by severe and sometimes devastating diseases. The topics of infection, sepsis,and SIRS have been reviewed and updated in keeping with the most recent information available, and particular focus has been directed to ethics
Keywords: Anesthesiology; Intensive / Critical Care Medicine; Critical care medicine; Notfalltherapie; Schmerztherapie; Anästhesie; Intensivtherapie; Konferenzschrift -- 1996 -- Triest